Penurunan Kadar Gula Darah Pasien DM Tipe 2 dengan Aktivitas Fisik - I Made Sundayana; I Dewa Ayu Rismayanti; Ida Ayu Putu Desta Candra Devi (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the relationship between physical activity and blood glucose levels in patients with type 2 diabetes. The research design used was a descriptive correlation with a cross-sectional approach. The results of the univariate analysis showed that the majority of respondents had moderate activity, as many as 19 people (43.2%), and the majority of respondents had poor blood sugar levels, namely 21 people (47.7%). The results of the bivariate analysis showed that p-value = 0.000 <0.05 with a correlation coefficient (r = 0.756). In conclusion, there is a relationship between physical activity and blood sugar levels in Type 2 DM patients. Keywords: Physical Activity, Type 2 Diabetes Mellitus, Blood Glucose